2018
DOI: 10.3390/rel9110356
|View full text |Cite
|
Sign up to set email alerts
|

“Enablement”—Spirituality Engagement in Pre-Registration Nurse Education and Practice: A Grounded Theory Investigation

Abstract: Historically, spirituality in nursing was considered a fundamental dimension, contributing to patients’ wellbeing. Accordingly, nurses are expected to attend to the spiritual needs of patients as a part of holistic nursing care, and pre-registration nurse education (that is undergraduate nurse education) has a responsibility to equip them to fulfil this aspect of their role. However, the content of spirituality in nurse education programmes lack structure and consistency, hence further investigation into the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…All stages of undergraduate training are represented Finnerty & Pope 2005 ; Rowan et al 2008 ; Schéle et al 2011 ; Nevalainen et al 2012 ; Hazel et al 2013 ; Hancock et al 2017 ; Friary et al 2018 ; Porteous and Machin 2018 ; Brondani & Donnelly 2020 ; Jowsey et al 2020 ; Kashbour et al 2019 Types of uncertainty Types of uncertainty can be categorised into: (i) uncertainty related to practice of healthcare itself; (ii) uncertainty related to the educational process; and (iii) uncertainty related to the self. The types of uncertainty that learners experienced, and their concerns around these, evolved as they progressed through their education Sobal & DeForge 1991 ; Biley & Smith 1999 ; Huijer et al 2000 ; Carr et al 2001 ; Warner et al 2001 ; Lingard et al 2003a ; Martinez & Lo 2008 ; Maudsley et al 2008 ; Rowan et al 2008 ; Ganesh & Ganesh 2010 ; Nevalainen et al 2010 ; Krupat et al 2011 ; Leh 2011 ; Schéle et al 2011 ; Teunissen & Westerman 2011 ; Watkins et al 2011 ; Nevalainen et al 2012 ; Hazel et al 2013 ; Landeen et al 2013 ; Curtis 2014 ; Kristiansson et al 2014 ; Nixon et al 2014 ; Bassett et al 2015 ; Ion et al 2015 ; Stone et al 2015 ; Ali et al 2017 ; Toivonen et al 2017 ; Dodgson et al 2018 ; Handwerker 2018 ; Lewinson et al 2018 ; Markey et al …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All stages of undergraduate training are represented Finnerty & Pope 2005 ; Rowan et al 2008 ; Schéle et al 2011 ; Nevalainen et al 2012 ; Hazel et al 2013 ; Hancock et al 2017 ; Friary et al 2018 ; Porteous and Machin 2018 ; Brondani & Donnelly 2020 ; Jowsey et al 2020 ; Kashbour et al 2019 Types of uncertainty Types of uncertainty can be categorised into: (i) uncertainty related to practice of healthcare itself; (ii) uncertainty related to the educational process; and (iii) uncertainty related to the self. The types of uncertainty that learners experienced, and their concerns around these, evolved as they progressed through their education Sobal & DeForge 1991 ; Biley & Smith 1999 ; Huijer et al 2000 ; Carr et al 2001 ; Warner et al 2001 ; Lingard et al 2003a ; Martinez & Lo 2008 ; Maudsley et al 2008 ; Rowan et al 2008 ; Ganesh & Ganesh 2010 ; Nevalainen et al 2010 ; Krupat et al 2011 ; Leh 2011 ; Schéle et al 2011 ; Teunissen & Westerman 2011 ; Watkins et al 2011 ; Nevalainen et al 2012 ; Hazel et al 2013 ; Landeen et al 2013 ; Curtis 2014 ; Kristiansson et al 2014 ; Nixon et al 2014 ; Bassett et al 2015 ; Ion et al 2015 ; Stone et al 2015 ; Ali et al 2017 ; Toivonen et al 2017 ; Dodgson et al 2018 ; Handwerker 2018 ; Lewinson et al 2018 ; Markey et al …”
Section: Resultsmentioning
confidence: 99%
“…Learners’ experiences of uncertainty, could be categorised as: (i) uncertainty related to the practice of healthcare itself (Ali et al 2017 ; Nixon et al 2014 ; Sobal and Deforge 1991 ; Carr et al 2001 ; Lingard et al 2003a ; Ganesh and Ganesh 2010 ; Markey et al 2018 ; Weurlander et al 2019 ); (ii) uncertainty related to the educational process (Biley and Smith 1999 ; Dodgson et al 2018 ; Mc Carthy et al 2018 ; Hazel et al 2013 ; Leh 2011 ; Stone et al 2015 ; Maudsley et al 2008 ; Gonzalo et al 2020 ); and (iii) uncertainty related to the learner’s self (Ganesh and Ganesh 2010 ; Toivonen et al 2017 ; Lingard et al 2003a ; Schéle et al 2011 ; Vae et al 2018 ; Young-Brice et al 2018 ; Handwerker 2018 ; Nevalainen et al 2010 , 2012 ; Huijer et al 2000 ; Weurlander et al 2019 ). Uncertainty emerged when learners experienced differences between themselves and others (Ion et al 2015 ; Watkins et al 2011 ; Lewinson et al 2018 ; Curtis 2014 ; Martinez and Lo 2008 ; Markey et al 2019 ), unfamiliar situations, or issues lacking easily distinguishable solutions (Ion et al 2015 ; Watkins et al 2011 ; Lewinson et al 2018 ; Matchim and Raetong 2018 ; Warner et al 2001 ; Toivonen et al 2017 ; Bassett et al 2015 ). Common places where this happened were at transitions (e.g., entry into undergraduate studies, movement into, and between, clinical placements) (Porteous and Machin 2018 ; McCarthy et al, 2018 ; Ingvarsson et al 2019 ; Teunissen and Westerman 2011 ), and in specific environments such as problem-based learning (Maudsley et al 2008 ; Landeen et al 2013 ; Rowan et al ...…”
Section: Resultsmentioning
confidence: 99%
“…spirituality. However, some nurses may be uncertain about the role of spirituality in nursing and how it can be integrated into their practice (Lewinson et al 2018). Clarke (2013) recognised spirituality as an intrinsic component of holistic care, a concept that has been detailed in several healthcare directives and guidelines (NHS Education for Scotland 2010, International Council of Nurses 2012).…”
mentioning
confidence: 99%
“…Clarke (2013) recognised spirituality as an intrinsic component of holistic care, a concept that has been detailed in several healthcare directives and guidelines (NHS Education for Scotland 2010, International Council of Nurses 2012). Similarly, Lewinson et al (2018) identified that spirituality has traditionally been considered a fundamental dimension of nursing practice, and one which contributes to patients' well-being. Nurses are expected to provide holistic care, which incorporates spirituality, and nurse education should prepare them for this role.…”
mentioning
confidence: 99%
See 1 more Smart Citation